HOLISTIC BIOLOGY: WHAT IT IS AND WHY IT MATTERS: with Fraser Watts and Michael J. Reiss, "Holistic Biology: What It Is and Why It Matters"; Michael Ruse, "The Christian's Dilemma: Organicism or Mechanism?"; David J. Depew and Bruce H. Weber, "Developmental Biology, Natural Selection, and the Conceptual Boundaries of the Modern Evolutionary Synthesis"; Ilya Gadjev, "Epigenetics, Representation, and Society"; Harris Wiseman, "Systems Biology and Predictive Neuroscience: A Double Helical Approach"; Richard Gunton and Francis Gilbert, "Laws in Ecology: Diverse Modes of Explanation for a Holistic Science"; and Niels Henrik Gregersen, The Exploration of Ecospace: Extending or Supplementing the Neo‐Darwinian Paradigm?. Issue 2 (June 2017) - Watts, Fraser; Reiss, Michael J.
Abstract: Recent developments toward a more holistic biology do not eliminate reductionism and determinism, but they do suggest more complex forms of them, in which there are multiple, interacting influences, as there are in complex or chaotic systems. Though there is a place in biology for both systemic and atomistic modes of explanation, for those with a theological perspective the shift to complex explanations in biology is often welcome. It suggests a more subtle view of divine action in which God's purposes are affected through engagement with the complex systems of creation rather than by discrete interventions. It also invites us to connect the biological interdependence with the interdependence in the nature and purposes of God, and it is consonant with a mystical vision of the unity of all things.